Comparative in vitro cytotoxicity of the emerging Fusarium mycotoxins beauvericin and enniatins to porcine intestinal epithelial cells. (November 2018) - Fraeyman, Sophie; Meyer, Evelyne; Devreese, Mathias; Antonissen, Gunther; Demeyere, Kristel; Haesebrouck, Freddy; Croubels, Siska
Abstract: The emerging Fusarium mycotoxins beauvericin (BEA) and enniatin (ENN) A, ENN A1, ENN B and ENN B1 gain increasing interest due to their highly prevalent contamination of cereals and cereal products. After oral intake, the gastro-intestinal tract is the first possible site of interaction. In the present in vitro study, the relative cytotoxicity of these mycotoxins towards proliferating and differentiated intestinal porcine epithelial cells of the jejunum (IPEC-J2) was evaluated using flow cytometric viability analysis. IPEC-J2 cells showed the highest sensitivity to BEA and ENN A. In proliferating cells, incubation for 24h with 10 μM BEA caused complete disruption, while the viability percentage declined to 32% after 24h of incubation with 10 μM ENN A. ENN A1 and ENN B1 were less cytotoxic with 87% and 93% viable cells after 24h of incubation with 10 μM ENN A1 and B1, respectively. ENN B was the least cytotoxic since incubation at concentrations up to 100 μM resulted in 83% viable proliferating cells. The same trend was observed for differentiated cells. The limited in vitro cytotoxic effect of ENN B on intestinal cells corroborates previous in vivo findings in broiler chicken in which dietary ENN B had minimal effect on intestinal morphometry. Highlights: Study of the cytotoxicity of BEA, ENN A, ENN A1, ENN B and ENN B1 to IPEC-J2 cells was studied using flow cytometric viability assessment. Proliferating IPEC-J2 cells were more prone to the cytotoxic effects of BEA. BEA > ENN A >> ENN A1 > ENN B1 >>> ENN B.